Aportaciones al estudio de la gestualidad en la iconografía románica hispana - Alicia Miguélez Cavero (Medievalista)
The aim of this paper is to set a series of general aspects related to the graphic representations of gestures in the Romanesque iconography of the Iberian Peninsula. This approach is based on the prior configuration of a gestural corpus, formed by attitudes, gestures and postures portrayed in the Romanesque Art of the Spanish kingdoms. The aspects dealt with affect the form, meaning and origin of gestures mainly.